Comparison of Physical Activity Patterns among Three Major Chronic Respiratory Diseases - Mantoani, Leandro Cruz [UNESP] (2023)
Although the level of physical activity in daily life (PADL) plays a vital role concerning the health of subjects with chronic lung diseases, it remains uncertain how PADL patterns compare among different conditions. This study’s objective was to compare the PADL levels of subjects with COPD, asthma and idiopathic pulmonary fibrosis (IPF); and to investigate PADL behaviour in different diseases’ severity. Stable subjects who had not undergone pulmonary rehabilitation in the previous year were included. Subjects were divided into two subgroups according to disease severity: mild/moderate and severe/very severe. The primary outcome was time spent in moderate-to-vigorous physical activities (MVPA) (Actigraph GT3x) measured during one week over 12 h/day; other assessments included pulmonary function, peripheral muscle strength and exercise capacity. Comparisons among subgroups were corrected for age, BMI and sex. The analysis involved 119 subjects (47 asthma, 48 COPD and 24 IPF). Subjects with asthma had higher PADL levels than those with COPD and IPF (MVPA 18(14–22) vs. 8(4–12) vs. 7(1–12) min/day, respectively; p ancova = 0.002). Subjects with severe/very severe IPF had the lowest PADL level among all subgroups. Adult subjects with asthma have higher PADL levels than those with COPD and IPF, whereas patients with severe and very severe IPF are the most physically inactive subjects.